## Related questions with answers

Question

Solve each equation and check the solution.

$-3(2 h-1)=3$

Solution

VerifiedStep 1

1 of 2The given equation is:

$-3\left(2h-1\right)=3$

Divide both sides by $-3$

$2h-1=-1$

Add $1$ to both sides

$2h=0$

Divide both sides by $2$

$h=0$

Check by replacing $h$ with $0$ in the original equation

$-3\left(2\times 0-1\right)=3$

$-3\left(0-1\right)=3$

$-3\left(-1\right)=3$

$3=3 \quad \text{true}$

The solution set is: $\{0\}$

## Create a free account to view solutions

By signing up, you accept Quizlet's Terms of Service and Privacy Policy

## Create a free account to view solutions

By signing up, you accept Quizlet's Terms of Service and Privacy Policy

## Recommended textbook solutions

#### MathMatters 3: An Integrated Program

1st Edition•ISBN: 9780078681783 (1 more)Lynch, Chicha, Olmstead, Eugene2,518 solutions

#### enVision Algebra 1

1st Edition•ISBN: 9780328931576Al Cuoco, Christine D. Thomas, Danielle Kennedy, Eric Milou, Rose Mary Zbiek3,653 solutions

#### Big Ideas Math Integrated Mathematics II

1st Edition•ISBN: 9781680330687Boswell, Larson4,539 solutions

## More related questions

1/4

1/7